Peningkatan Proses dan Hasil Belajar IPAS Menggunakan Model Somatic, Auditory, Visual, Intellectual (SAVI) dengan Media Puzzle di Kelas VI SDN 012/II Empelu - Ovy Lestari; Sundahry Sundahry; Elvima Nofrianni (Master Journal of Future Education, 2025)
This Classroom Action Research conducted in Grade VI of SDN 012/II Empelu was motivated by preliminary observations, which indicated the low quality of both the learning process and student outcomes. This could be seen from learning activities that were not yet aligned with the requirements of the Merdeka Curriculum and from the average scores of daily tests that were still below the Minimum Mastery Criteria (KKTP). To address this issue, the SAVI (Somatic, Auditory, Visual, Intellectual) learning model was implemented using “puzzle” media. The purpose of this study was to describe the improvement of the learning process and student outcomes through the application of the SAVI model on the topic How Our Body Moves.The research method used was Classroom Action Research (CAR), carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The subjects of this study were 25 Grade VI students of SDN 012/II Empelu, while the object of the study was the implementation of the SAVI (Somatic, Auditory, Visual, Intellectual) model in IPAS learning. Data collection techniques included observation, learning outcome tests, and documentation. Data were analyzed using descriptive qualitative and quantitative methods. The results showed that the implementation of the SAVI model with puzzle media was categorized as very good. In terms of process, teacher and student engagement improved from the “good” category in Cycle I to “very good” in Cycle II. In terms of learning outcomes, the students’ average score increased from 70.4% in Cycle I to 86.3% in Cycle II, with the percentage of learning mastery rising from 28% to 80%. The application of the SAVI (Somatic, Auditory, Visual, Intellectual) model proved effective in enhancing student activeness and conceptual understanding of IPAS.